Analyzing the potential and progress of distributed generation applications in Saudi Arabia: The case of solar and wind resources - Ramlia, Makbul A.M.; Ssennoga, Twahab; Zakariya, Al-Hamouzc (Renewable and sustainable energy reviews, 2017)
In this paper, the potential of solar and wind energy-based distributed generation (DG) in Saudi Arabia is simultaneously analyzed with the aim of maximizing the utilization of available resources. It begins with an analysis of DG application potential for wind and solar energy resources in various regions of Saudi Arabia. The progress of DG applications in terms of research, planning, and exploitation of wind and solar energy resources is then presented. An assessment of the DG contribution to the energy sector of Saudi Arabia has been conducted and the barriers and challenges for the implementation of DG systems in the country are discussed with suggested measures to overcome the challenges. The main findings are that with the huge potential of wind and solar resources for DG applications the country has targeted 50 GW of wind and solar capacity by the year 2040. The Saudi government is expected to provide full support in the form of financial incentives for solar and wind energy projects in order to boost renewable energy development.
Keywords: Distributed generation; Solar energy; Wind energy; Energy resource potential analysis